A new green index as an overall quantitative green performance indicator of a facility - Mustapha, M. A. (Springer Verlag, 2016)
Green assessment tools such as the Building Research Establishment Environmental Assessment Method, Leadership in Energy and Environmental Design, Comprehensive Assessment System for Building Environmental Efficiency, GREEN STAR and HK-BEAM have been used worldwide. These tools, which utilise qualitative, credit-based rating system have several limitations. Firstly, they can only provide a relative measure of the greenness of a facility. Secondly, there is the possibility that the ratings assigned may differ from one user to another depending on the needs and priorities of an organisation, a country, or a region. Several studies have also highlighted that such credit-based systems involve piece-meal (Zuo and Zhou in Renew Sustain Energy Rev 30:271–281, 2014), as opposed to integrated evaluation of the green criteria, and the greenness of a facility. This paper proposes a new Green Index (GI) as a tool for assessing the level of greenness of a facility that overcomes the aforementioned limitations. The use of stock market composite index as a basis for the GI development has enabled an established tool for assessing stock market performances to progress into the domain of industrial and commercial facility management. Development of the GI involves two steps, namely the development of a weighting scheme using the factor analysis approach, followed by the composite GI formulation that is based on the stock market composite index. The developed Green Index is based on quantitative analysis and measurement of parameters, and hence, reflect the actual measure of the overall impact of a facility on the environment. With only a single indicator to represent multiple green elements, it makes it easier for facility managers to effectively and quantitatively monitor, analyse, compare and benchmark the actual level of greenness of facilities in new systems designs or a retrofit or conservation programme.